Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Characterisation of past marine heatwaves around South Pacific Island countries: what really matters? - Shilpa Lal; Sophie Cravatte; Christophe Menkes; Jed Macdonald; Romain Le Gendre; Ines Mangolte; Cyril Dutheil; Neil J. Holbrook; Simon Nicol (Ocean Science, 2026)
Marine heatwaves (MHWs) can have devastating and lasting impacts on marine ecosystems. We investigated past MHW characteristics around 12 southwestern Pacific Island countries and territories (PICTs) using two observed sea surface temperature products and an ocean reanalysis product. PICTs are highly dependent on their marine resources for their livelihoods: a better understanding of MHW characteristics is needed for planning and adaptation to risks associated with MHWs. Our research builds on previous studies where MHWs have been detected and described using a point-based definition. We first revisit past MHW characteristics based on their spatial extent, vertical extent and seasonality. We show that filtering MHWs by size (spatial extent) and seasonality can greatly affect their characterisation and help trace their physical drivers. We then characterise past events inside each Exclusive Economic Zone (EEZ) and at the coast with MHW indices tailored to benefit Pacific Island stakeholders. We consider two types of events: large-scale events, covering a large part of the EEZ, likely to affect pelagic fisheries, and events affecting coastal zones and ecosystems. We distinguish between events occurring in the hot season (November to April), and in the cold season (May to October). We show that all 12 PICTs experienced MHWs in the past 30 years that are getting more frequent with greater spatial extents, longer durations, explained by the long-term warming trend in sea surface temperature, but with lower maximum intensity. New Caledonia, Vanuatu, Fiji and Tonga appear to be more exposed to MHWs with longer duration, higher maximum intensity, and deeper extent compared to other countries.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Linear, nonlinear, parametric and nonparametric regression models for nonstationary flood frequency analysis - Mengzhu Chen; Konstantinos Papadikis; Changhyun Jun; Neil Macdonald (Journal of Hydrology, 2023)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Factors affecting the occurrence and activity of clouded leopards, common leopards and leopard cats in the Himalayas - Özgün Emre Can; Bhupendra Prasad Yadav; Paul J. Johnson; Joanna Ross; Neil D’Cruze; David W. Macdonald (Biodiversity and Conservation, 2020)
Clouded leopards are one of the least known of larger felids and were believed to be extinct in Nepal until 1987. They are particularly interesting because their Asian range spans a diversity of habitats in the fastest disappearing forests in the world and encompasses a guild which differs in composition from place to place. As a part of a wider camera-trapping study of this guild, involving 2948 camera traps at 45 sites in nine countries, and paralleling a similar study of the Sunda clouded leopard including a further 1544 camera traps spanning 22 sites distributed across two countries, we deployed 84 pairs of camera traps for 107 days in 2014 and 2015 at Langtang National Park, Nepal between 1823 and 3824 m a.s.l. within a grid encompassing c. 120 km 2 . We documented the presence of clouded leopards for the first time at an altitude as high as 3498 m a.s.l. Naïve occupancy for clouded leopard was 8.6% (correcting for detection, 10.1%). Clouded leopards were least active in the middle of the day, and largely crepuscular and nocturnal, as were the common leopards and leopard cats. The peak of clouded leopard activity overlapped with that of musk deer. Prey species for both clouded leopard and common leopard were available across the elevation range studied although the availability of some prey species declined as elevation increased, whereas Himalayan serow, Himalayan goral, and musk deer showed no association with elevation. Before this study, there was no hard evidence that clouded leopards occurred above 2300 m a.s.l., having documented them at almost 4000 m a.s.l. in the Himalayas, we emphasise the importance of this extreme portion of the species’ range where climate is likely to change more rapidly and with greater consequences, than the global average. The discovery of clouded leopards in Langtang National Park considerably extends their known range, and raises the possibility that they occur from the Terai in southern Nepal up to the Nepal-Tibet (China) border in the north. Insofar as this study has extended the known extreme boundary of the clouded leopard’s geographic range to encompass Langtang National Park in the Nepali Himalayas.

Multi‐century trends to wetter winters and drier summers in the England and Wales precipitation series explained by observational and sampling bias in early records - Conor Murphy; Robert L. Wilby; Tom K. R. Matthews; Peter Thorne; Ciaran Broderick; Rowan Fealy; Julia Hall; Shaun Harrigan; Phil Jones; Gerard McCarthy; Neil MacDonald; Simon Noone; et al. (International Journal of Climatology, 2020)
Globally, few precipitation records extend to the 18th century. The England Wales Precipitation (EWP) series is a notable exception with continuous monthly records from 1766. EWP has found widespread use across diverse fields of research including trend detection, evaluation of climate model simulations, as a proxy for mid‐latitude atmospheric circulation, a predictor in long‐term European gridded precipitation data sets, the assessment of drought and extremes, tree‐ring reconstructions and as a benchmark for other regional series. A key finding from EWP has been the multi‐centennial trends towards wetter winters and drier summers. We statistically reconstruct seasonal EWP using independent, quality‐assured temperature, pressure and circulation indices. Using a sleet and snow series for the UK derived by Profs. Gordon Manley and Elizabeth Shaw to examine winter reconstructions, we show that precipitation totals for pre‐1870 winters are likely biased low due to gauge under‐catch of snowfall and a higher incidence of snowfall during this period. When these factors are accounted for in our reconstructions, the observed trend to wetter winters in EWP is no longer evident. For summer, we find that pre‐1820 precipitation totals are too high, likely due to decreasing network density and less certain data at key stations. A significant trend to drier summers is not robustly present in our reconstructions of the EWP series. While our findings are more certain for winter than summer, we highlight (a) that extreme caution should be exercised when using EWP to make inferences about multi‐centennial trends, and; (b) that assessments of 18th and 19th Century winter precipitation should be aware of potential snow biases in early records. Our findings underline the importance of continual re‐appraisal of established long‐term climate data sets as new evidence becomes available. It is also likely that the identified biases in winter EWP have distorted many other long‐term European precipitation series.

Dry weather fears of Britain’s early ‘industrial’ canal network - Alice Harvey-Fishenden; Neil Macdonald; James P. Bowen (Regional Environmental Change, 2019)

Predicting contemporary range‐wide genomic variation using climatic, phylogeographic and morphological knowledge in an ancient, unglaciated landscape - Rachel M. Binks; Neil Gibson; Kym M. Ottewell; Bronwyn Macdonald; Margaret Byrne (Journal of Biogeography, 2019)
Aim Understanding the spatial distribution of genetic variation across a species’ range is a central tenet in evolutionary biology and the ability to predict such patterns is valuable to conservation management. Genetic diversity and differentiation may be explained by present‐day niche centrality, historical processes, or morphological variation across a species’ range, yet few studies evaluate these factors concurrently. Moreover, there is a particular lack of knowledge of the influence of these factors in ancient, unglaciated landscapes of the Southern Hemisphere. We investigate these concepts for their influence upon spatial patterns of genetic variation in a widespread plant species in a southern biodiversity hotspot. Location South‐western Australia. Taxon Calothamnus quadrifidus . Methods We use genotyping‐by‐sequencing to assess genome‐wide diversity and differentiation across the range of Calothamnus quadrifidus , a morphologically variable species that occurs over a wide geographic range in an ancient, unglaciated landscape. We correlated the patterns of genetic diversity and differentiation with those predicted under four hypotheses regarding effects of geographic centrality, climatic centrality, historical phylogeography and morphological subspecies. Results We found spatial variation in genetic diversity and strong population structuring, and while each hypothesis was consistent with some of these patterns, no hypothesis predicted the full extent of genetic diversity or structure in C. quadrifidus . Main conclusions Our results are indicative of a complex evolutionary history, with multiple factors shaping contemporary genetic variation in C. quadrifidus over time, rather than any one major driving factor. This is enabled by the greater capacity to build complex evolutionary signals in ancient, more stable landscapes like the southwest of Western Australia that are not as predictable as those within the younger, post‐glacial landscapes of the Northern Hemisphere. Finally, our study demonstrates the importance of using an interdisciplinary approach to understanding the spatial patterns of genetic variation across species’ ranges and the influence of ecological, geographical and historical factors.

Resistin and NGAL are associated with inflammatory response, endothelial activation and clinical outcomes in sepsis - Stephen P. J. Macdonald; Erika Bosio; Claire Neil; Glenn Arendts; Sally Burrows; Lisa Smart; Simon G. A. Brown; Daniel M. Fatovich (Inflammation Research, 2017)

Quantifying system disturbance and recovery from historical mining-derived metal contamination at Brotherswater, northwest England - Daniel N. Schillereff; Richard C. Chiverrell; Neil Macdonald; Janet M. Hooke; Katharine E. Welsh (Journal of Paleolimnology, 2016)

Erratum to: Balanced Sediment Fluxes in Southern California’s Mediterranean-Climate Zone Salt Marshes - Jordan A. Rosencranz; Neil K. Ganju; Richard F. Ambrose; Sandra M. Brosnahan; Patrick J. Dickhudt; Glenn R. Guntenspergen; Glen M. MacDonald; John Y. Takekawa; Karen M. Thorne (Estuaries and Coasts, 2016)

Balanced Sediment Fluxes in Southern California’s Mediterranean-Climate Zone Salt Marshes - Jordan A. Rosencranz; Neil K. Ganju; Richard F. Ambrose; Sandra M. Brosnahan; Patrick J. Dickhudt; Glenn R. Guntenspergen; Glen M. MacDonald; John Y. Takekawa; Karen M. Thorne (Estuaries and Coasts, 2016)

Aflibercept exhibits VEGF binding stoichiometry distinct from bevacizumab and does not support formation of immune-like complexes - Douglas A. MacDonald; Joel Martin; Kathir K. Muthusamy; Jiann-Kae Luo; Erica Pyles; Ashique Rafique; Tammy Huang; Terra Potocky; Yang Liu; Jingtai Cao; Françoise Bono; Nathalie Delesque; et al. (Angiogenesis, 2016)

Clouded in mystery: the global trade in clouded leopards - Neil D’Cruze; David W. Macdonald (Biodiversity and Conservation, 2015)

Local-level determinants of wildcat occupancy in Northeast Scotland - André P. Silva; Luís M. Rosalino; Paul J. Johnson; David W. Macdonald; Neil Anderson; Kerry Kilshaw (European Journal of Wildlife Research, 2013)

Trends in flood seasonality of the River Ouse (Northern England) from archive and instrumental sources since AD 1600 - Neil Macdonald (Climatic Change, 2012)

Reassessment of flood frequency using historical information for the River Ouse at York, UK (1200–2000) - Neil Macdonald; Andrew R. Black (Hydrological Sciences Journal, 2010)

European floods during the winter 1783/1784: scenarios of an extreme event during the ‘Little Ice Age’ - Rudolf Brázdil; Gaston R. Demarée; Mathias Deutsch; Emmanuel Garnier; Andrea Kiss; Jürg Luterbacher; Neil Macdonald; Christian Rohr; Petr Dobrovolný; Petr Kolář; Kateřina Chromá (Theoretical and Applied Climatology, 2010)

Isometric handgrip exercise improves acute neurocardiac regulation - Philip J. Millar; Maureen J. MacDonald; Steven R. Bray; Neil McCartney (European Journal of Applied Physiology, 2009)

Isometric handgrip training improves local flow-mediated dilation in medicated hypertensives - Cheri L. McGowan; Adrienne Visocchi; Martha Faulkner; Robin Verduyn; Mark Rakobowchuk; Andrew S. Levy; Neil McCartney; Maureen J. MacDonald (European Journal of Applied Physiology, 2008)

Potential impact of ABCB1 (p-glycoprotein) polymorphisms on avermectin toxicity in humans - Neil Macdonald; Alex Gledhill (Archives of Toxicology, 2007)

Isometric handgrip training improves local flow-mediated dilation in medicated hypertensives - Cheri L. McGowan; Adrienne Visocchi; Martha Faulkner; Robin Verduyn; Mark Rakobowchuk; Andrew S. Levy; Neil McCartney; Maureen J. MacDonald (European Journal of Applied Physiology, 2007)

Isometric handgrip training improves local flow-mediated dilation in medicated hypertensives - Cheri L. McGowan; Adrienne Visocchi; Martha Faulkner; Robin Verduyn; Mark Rakobowchuk; Andrew S. Levy; Neil McCartney; Maureen J. MacDonald (European Journal of Applied Physiology, 2006)

Metabolic poise in the North Atlantic Ocean diagnosed from organic matter transports - Dennis A. Hansell; Hugh W. Ducklow; Alison M. Macdonald; Molly O‐Neil Baringer (Limnology and Oceanography, 2004)
Recently there has been discussion about the metabolic state of the ocean, with arguments questioning whether the open ocean is net autotrophic or net heterotrophic. Accurately determining the metabolic balance of a marine system depends on fully defining the system being evaluated and on quantifying the inputs and outputs to that system. Here, a net northward transport of dissolved organic carbon (DOC) (across 24.5°N) of 3.3 ± 1.9 Tmol C yr −1 was determined using basin‐wide transport estimates of DOC. This flux, coupled with DOC inputs from the Arctic Ocean (2.2 ± 0.8 Tmol C yr −1 ), the atmosphere (0.6 ± 0.08 Tmol C yr −1 ), and rivers (3.1 ± 0.6 Tmol C yr −1 ), indicates net heterotrophy in the North Atlantic (full depth, 24.5–72°N) of 9.2 ± 2.2 Tmol C yr −1 . This rate is small ( −1 ) and consumption (production : respiration of 0.98), indicating that the North Atlantic is essentially metabolically balanced and that autochthonous production is remineralized within the basin. The upper layer of the subtropical gyre has previously been reported to exhibit high rates of net heterotrophy, but our analysis does not support those findings. Instead, allochthonous inputs of organic carbon to the upper subtropical gyre are an order of magnitude less than required by the elevated rates of net heterotrophy reported. We find, too, that net mineralization of allochthonous DOC within the basin could account for 10% of the preindustrial inorganic carbon exported from the basin to the south. Two factors, the import of organic matter and the unique thermohaline circulation pattern of the North Atlantic, are primary in ensuring net heterotrophy in the basin.

Quantitative proteomic analysis of mouse liver response to the peroxisome proliferator diethylhexylphthalate (DEHP) - Neil Macdonald; Stephan Chevalier; Robert Tonge; Matthew Davison; Rachel Rowlinson; Janice Young; Steve Rayner; Ruth Roberts (Archives of Toxicology, 2001)

Species differences in response to diethylhexylphthalate: suppression of apoptosis, induction of DNA synthesis and peroxisome proliferator activated receptor alpha-mediated gene expression - Susan C. Hasmall; Neil H. James; Neil Macdonald; Anthony R. Soames; Ruth A. Roberts (Archives of Toxicology, 2000)

Suppression of apoptosis and induction of DNA synthesis in vitro by the phthalate plasticizers monoethylhexylphthalate (MEHP) and diisononylphthalate (DINP): a comparison of rat and human hepatocytes in vitro - Susan C. Hasmall; Neil H. James; Neil Macdonald; Douglas West; Stephan Chevalier; Sabina C. Cosulich; Ruth A. Roberts (Archives of Toxicology, 1999)

Hypotension following mild bouts of resistance exercise and submaximal dynamic exercise - Jay R. MacDonald; J. Duncan MacDougall; Stephen A. Interisano; Kelly M. Smith; Neil McCartney; John S. Moroz; Ed V. Younglai; Mark A. Tarnopolsky (European Journal of Applied Physiology, 1999)